Mechanical anisotropy of deep ice core samples by uniaxial compression tests (scientific paper) - Miyamoto, Atsushi; Shimohara, Kimiko; Hyakutake, Kinji; Shoji, Hitoshi; Narita, Hideki; Hondoh, Takeo (2003)
P(論文) Mechanical anisotropy of ice core samples has been observed in various uniaxial compression tests. The c-axis orientation distribution is the primary influence on the mechanical behavior of ice cores. A strong single-maximum fabric pattern is observed in the deep parts of the ice sheet. In this region, polycrystalline ice is very hard along the vertical axis; however, it easily shears along the horizontal plane. Thus, by acquiring the distribution of c-axis orientations throughout the ice sheet, the mechanical anisotropy of ice sheet flow behavior can be understood. Analysis of fabric measurements on the Dye 3, GRIP, and Dome F ice cores suggests that the c-axis orientation distribution depends primarily on vertical strain. Therefore, if the ice thickness at some point in the ice sheet is known, it should be possible to predict the distribution of c-axis orientations at that depth. Uniaxial compression tests were carried out along various directions of the Dye 3, GRIP, and Dome F ice cores. A contour map of mechanical anisotropy was then made to relate the compression direction to the vertical strain. This clarified the flow enhancement factor in every compression direction at a given vertical strain. departmental bulletin paper